The Grand Ensemble of Orly-Choisy-le-Roi: the Construction, Deconstruction and Reconstruction of a Neighbourhood - Caterina Quaglio (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
How is the scale and perimeter of a neighbourhood defined? Shifting the attention from the policy dimension to their actual implementation in a specific place, the article questions the evolution of the notion of neighbourhood by retracing the history of the Grand Ensemble Orly-Choisy-le-Roi, from its construction to the successive redevelopment programmes carried out almost uninterruptedly until today. Throughout this time, the neighbourhoods of the Grand Ensemble have been constructed, deconstructed and reconstructed both in the physical environment and in local narratives and imaginaries. Consequently, relying on the local dimension as a lens to address broader phenomena, the text highlights not only the discrepancies in time and meaning characterizing different phases and approaches, but also the elements of continuity that become manifest at the “micro” scale of the Grand Ensemble.